Sodium Phosphate Supplementation and Time Trial Performance in Female Cyclists - Buck, Christopher L. (Asist Group, 2014)
This study investigated the effects of three doses of sodium phosphate (SP) supplementation on cycling 500 kJ (119.5 Kcal) time trial (TT) performance in female cyclists. Thirteen cyclists participated in a randomised, Latin-square design study where they completed four separate trials after ingesting either a placebo, or one of three different doses (25, 50 or 75 mg·kg(-1) fat free mass: FFM) of trisodium phosphate dodecahydrate which was split into four equal doses a day for six days. On the day after the loading phase, the TT was performed on a cycle ergometer. Serum phosphate blood samples were taken at rest both before and after each loading protocol, while a ~21 day washout period separated each loading phase. No significant differences in TT performance were observed between any of the supplementation protocols (p = 0.73) with average completion times for the 25, 50 or 75 mg·kg(-1) FFM being, 42:21 ± 07:53, 40:55 ± 07:33 and 40:38 ± 07:20 min respectively, and 40:39 ± 07:51 min for the placebo. Likewise, average and peak power output did not significantly differ between trials (p = 0.06 and p = 0.46, respectively). Consequently, 500 kJ cycling TT performance was not different in any of the supplementation protocols in female cyclists.